European experience in preventing and combating crime by customs authorities and the possibility of its use in Ukraine - Andrii Volodymyrovych Nosach; Mykhailo Ihorevych Fialka; Ruslan Anatolevich Cherkasskyi; Selezen Svitlana Volodymyrivna (Ius Humani. Jornal do direito, 2022)
Nowadays, quite effective systems have been formed in the world to combat and prevent customs crimes in general and by customs authorities, however, the experience of not all states is positive. The article, based on the analysis of the scientific views of scholars, summarizes the experience of the leading European countries (on the example of Great Britain, France, Germany) in the field of preventing and combating crime by customs authorities. Both positive and negative aspects of the experience in the field of combating crime in these countries are singled out. The analysis of foreign experience in preventing and combating crime by customs authorities made it possible to formulate the following points that should be used by the domestic legislator: firstly, a high level of material, technical and financial support of the customs authorities, which makes it possible to more quickly respond to existing challenges; secondly, the customs authorities of the vast majority of countries have a wide range of powers in the context of the implementation of intelligence operations; thirdly, a high level of interaction and exchange of information between the EU countries in the framework of combating customs crime; fourthly, an important aspect of combating and preventing customs crime is the professional training of customs personnel; fifthly, on the example of foreign countries in Ukraine, it was expedient to strengthen administrative and criminal liability for violation of customs legislation; sixth, a high level of social and financial support for customs employees.